IMPLEMENTASI ALGORITMA FUZZY C-MEANS UNTUK MEMPREDIKSI FAKTOR SISWA MEMBOLOS - sulisdianto, dwi (Jurnal RESTIKOM : Riset Teknik Informatika dan Komputer, 2019)
Truant behavior does not merely affect student learning achievement, but is also classified as one form of juvenile delinquency. Adolescents' self-esteem is a deviant behavior because there are behavioral deviations from various social rules or from prevailing social values and norms and become a source of problems that can endanger the upholding of the social system. ditching activities as well as things that can set the background for other problems arise. Evidently, truant students often get involved with things that tend to harm themselves and others such as smoking, brawls, and free association. The mistake of truant behavior is mostly borne by students involved in skipping school. When case after case ditching can be revealed students are the ones who become the burden of mistakes. This is an attitude that does not support their potential will only add to their problems. Therefore, this research requires indicators and parameters in finding the solution to the problem of influencing students. For data processing, this study uses the Fuzzy C-Means method. This method was chosen because the placement of the cluster center is more appropriate than the other cluster methods.Cluster 1 is 70 students (56.4%), Cluster 2 is 25 and Cluster 3 is 29 students (23.4%).